Chris Wisbey interviewed by Rob Willis in the Rob and Olya Willis folklore collection - Wisbey, Chris, 1954-; Willis, Rob, 1944- (2011)
Folkloric recording. Chris Wisbey is the popular presenter of ABC radio's statewide Tasmanian weekend show. He talks about his family background and growing up in Taroona, Tas.; the family farm in Richmond; his schooling and tertiary education; his love of boats and the sea; working as a miner on King Island and at Rosebery and Williamsford; the mining boom in the late 1970s; living conditions; Theiss Bros.; Owen Adcock; moving to Townsville, Qld.; study at the Townsville College of Advanced Education; working for the ABC in Townsville; returning to Tasmania and working as a rural reporter on 'Morning Extra' in Launceston; presenting on 'Australian All Over' radio program in Sydney; leaving the program to work in northern NSW; working overseas for Austrian News on Radio Blue Danube, based in Vienna: his european experiences; returning to Tasmania to live; working for the ABC presenting Saturday and Sunday mornings; changes in technology and the importance of archiving; the many great stories that need to be told and the content of his program; his involvement with the cherry industry; his leisure activities.
Recorded with Olya Willis.
Summary accompanied by photographs.
Recorded on 27 February 2011 in Hobart, Tas.
Mode of access: Online.
Timed summary (4 p.)
Keywords: Wisbey, Chris, -- 1954- -- Interviews; Australian Broadcasting Commission; Broadcasters -- Tasmania -- Interviews; Broadcasters